High‐Performance and Stable Perovskite Solar Cells Based on Dopant‐Free Arylamine‐Substituted Copper(II) Phthalocyanine Hole‐Transporting Materials. Issue 26 (27th May 2019) - Feng, Yaomiao; Hu, Qikun; Rezaee, Ehsan; Li, Minzhang; Xu, Zong‐Xiang; Lorenzoni, Andrea; Mercuri, Francesco; Muccini, Michele
Abstract: A power conversion efficiency (PCE) as high as 19.7% is achieved using a novel, low‐cost, dopant‐free hole transport material (HTM) in mixed‐ion solution‐processed perovskite solar cells (PSCs). Following a rational molecular design strategy, arylamine‐substituted copper(II) phthalocyanine (CuPc) derivatives are selected as HTMs, reaching the highest PCE ever reported for PSCs employing dopant‐free HTMs. The intrinsic thermal and chemical properties of dopant‐free CuPcs result in PSCs with a long‐term stability outperforming that of the benchmark doped 2, 2′, 7, 7′‐Tetrakis‐( N, N ‐di‐ p ‐methoxyphenylamine)‐9, 9′‐Spirobifluorene (Spiro‐OMeTAD)‐based devices. The combination of molecular modeling, synthesis, and full experimental characterization sheds light on the nanostructure and molecular aggregation of arylamine‐substituted CuPc compounds, providing a link between molecular structure and device properties. These results reveal the potential of engineering CuPc derivatives as dopant‐free HTMs to fabricate cost‐effective and highly efficient PSCs with long‐term stability, and pave the way to their commercial‐scale manufacturing. More generally, this case demonstrates how an integrated approach based on rational design and computational modeling can guide and anticipate the synthesis of new classes of materials to achieve specific functions in complex device structures. Abstract : Highly‐efficient, low‐cost, solution‐processed perovskite solar cells, exhibiting remarkable environmental stability, are reported. The fabrication strategy relies on the rational design of the molecular structure of arylamine‐substituted copper(II) phthalocyanine (CuPc) derivatives, which are used as dopant‐free hole‐transport materials. The resulting devices reach a power conversion efficiency of 19.7% and display enhanced long‐term stability with respect to standard (doped) materials.